2022
DOI: 10.18502/ijps.v18i1.11415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Noninvasive Brain Stimulation with Weak Non-Constant Current Stimulation Approaches

Abstract: Objective: Non-constant current stimulation (NCCS) is a neuromodulatory method in which weak alternating, pulsed or random currents are delivered to the human head via scalp or earlobe electrodes. This approach is widely used in basic and translational studies. However, the underlying mechanisms of NCCS, which lead to biological and behavioral effects in the brain, remain largely unknown. In this review, we characterize NCCS techniques currently being utilized in neuroscience investigations, including transcra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The use of neurobiology technology to assess Dyslexia, however, has the advantage of being easier to judge on a scale, and the bioinformatics can break through the linguistic limitations, and the bioinformatics does not depend on the child's understanding of the test questions to detect the child's risk of Dyslexia before the cognitive test (Carrasco & Carrasco, 2022). In the field of biological neurology, current research on Dyslexia has evolved from focusing on the neocortex of the brain and showing changes in the degree of asymmetry in the temporal plane at the structural level to finding abnormal white matter integrity along the left arcuate fasciculus (Guadalupe et al, 2015, Zhao et al, 2016Bahrami et al, 2021;Vellasamy et al, 2022;Shirehjini et al, 2023). However, within the field of neurobiology, there is no consensus on which neurobiological signals can accurately predict and determine Dyslexia (Norton et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The use of neurobiology technology to assess Dyslexia, however, has the advantage of being easier to judge on a scale, and the bioinformatics can break through the linguistic limitations, and the bioinformatics does not depend on the child's understanding of the test questions to detect the child's risk of Dyslexia before the cognitive test (Carrasco & Carrasco, 2022). In the field of biological neurology, current research on Dyslexia has evolved from focusing on the neocortex of the brain and showing changes in the degree of asymmetry in the temporal plane at the structural level to finding abnormal white matter integrity along the left arcuate fasciculus (Guadalupe et al, 2015, Zhao et al, 2016Bahrami et al, 2021;Vellasamy et al, 2022;Shirehjini et al, 2023). However, within the field of neurobiology, there is no consensus on which neurobiological signals can accurately predict and determine Dyslexia (Norton et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous literatures, aggression is typically categorized as physical, such as hitting, kicking, and spitting; verbal, such as shouting, threatening, and saying hurtful words; and relational, such as slandering someone and causing harm to social relationships (Coyne et al, 2010;Zhang et al, 2016;Ettekal & Ladd, 2017). Thereinto, it was found that physical and verbal aggression are regarded as overt aggression (Putallaz et al, 2008;Smith et al, 2009) (see in Figure 1).…”
Section: Findings Aggressionmentioning
confidence: 99%
“…Many scholars have explored that low self-control is linked with aggressive and risky behaviors over time (Pratt et al, 2014;Reisig & Pratt, 2011;Shirehjini et al, 2023). Selfcontrol is found to be inversely related to self-reported aggression (Özdemir et al, 2013), laboratory aggression (Denson et al, 2011), driving aggression (Ellwanger & Pratt, 2014), aggressive ideation and aggressive behavior (Murray et al, 2016), and direct aggression (Meldrum et al, 2018).…”
Section: Self-control and Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through tDCS, a low-intensity current of often less than or equal to 2 milliamps (mA) is applied at the scalp level ( 17 ). However, it is important to note that only a fraction of this current, estimated in the order of tens of microamperes, actually reaches the neural system, typically targeting areas like the DLPFC ( 18 , 19 ). Therefore, tDCS is not considered an invasive procedure ( 20 ).…”
mentioning
confidence: 99%